Awareness and preventive practice regarding osteoporosis among women in a community, Lalitpur (Journal of Patan Academy of Health Sciences, 2022)
Introduction: Osteoporosis is a major public health problem globally that can break a bone from a minor fall, or even from simple actions like sneezing. This study sim to assess the awareness and preventive practice of osteoporosis among community women.Method: An analytical cross-sectional study was conducted. The multistage sampling technique was used to select the sample from women 18-65 years from ward no. 16 of Lalitpur, Kathmandu, Nepal. Data were collected by using a semi-structured questionnaire to obtain socio-demographic variables. The Osteoporosis knowledge assessment tool (OKAT) and Osteoporosis Knowledge tool (OKT) were modified to assess the level of awareness and the Likert scale was used to assess the level of preventive practice. The SPSS 16 was used for analysis. The association and correlation between variables were measured by chi-square and Pearson correlation coefficient respectively.Result: The majority 167(74.2%) of the respondents had an adequate level of awareness. The awareness had a statistically significant association with educational status (p=0.042). More than half 119(52.9%) of respondents had a poor level of preventive practice. There is a low but significant positive correlation between the level of awareness and level of total preventive practice (r = 0.251).Conclusion: There was an adequate level of awareness among respondents, but had a poor level of preventive practice. There was a low but positive correlation between awareness and preventive practice.